Deep‐blue Fluorophores Based on Phenanthroimidazole Integrated with Benzo[d]thiazole: Experimental and Theoretical Investigation. Issue 27 (14th July 2022) - Girase, Jaipal D.; Shahnawaz,; Jou, Jwo‐Huei; Vaidyanathan, Sivakumar
Abstract: Three deep‐blue emissive donor‐acceptor (D−A) fluorophores, 2‐(4′‐(1‐(4‐(tert‐butyl)phenyl)‐1 H ‐phenanthro[9, 10‐ d ]imidazol‐2‐yl)‐[1, 1′‐biphenyl]‐4‐yl)benzo[ d ]thiazole (PTPISN ), 2‐(4′‐(1‐(3‐(trifluoromethyl)phenyl)‐1 H ‐phenanthro[9, 10‐ d ]imidazol‐2‐yl)‐[1, 1′‐biphenyl]‐4‐yl)benzo[ d ]thiazole (m‐CFPISN ) and 3‐(2‐(4′‐(benzo[d]thiazol‐2‐yl)‐[1, 1′‐biphenyl]‐4‐yl)‐1 H ‐phenanthro[9, 10‐d]imidazol‐1‐yl)benzonitrile (m‐CNPISN ) based on benzothiazole with varying substituents at N1‐position to tune the properties of the materials were designed and synthesized. The synthesized fluorophores were structurally confirmed by spectroscopic techniques. All the fluorophores exhibited good thermal properties with high thermal degradation temperatures. An optical study reveals that the fluorophores are capable of emitting in the blue spectral region in solution and solid. The quantum chemical investigations were also performed with the aim to understand the electronic structures of the fluorophores. Further, solution‐processed OLED device was fabricated by using PTPISN as an emissive dopant and found that bright deep‐blue electroluminescence with CIEy of (∼0.08). These results suggest that the introduction of benzothiazole moiety is a promising design strategy for obtaining new deep‐blue emitters. Abstract : A series of deep blue fluorophores based on benzothiazole as acceptor core was designed and synthesized. All the fluorophores shows deep blue emission, high PLQY, and positive solvatochromism effect. The doped device based on PTPISN shows deep blue EL emission with CIE coordinates of (0.15, 0.08) with good EL performance of PEmax, CEmax, and EQEmax of 0.2 lm/W, 1.1 cd/A, and 1.3 % at the brightness of 1000 cd/m 2 .